Is There An Association Between Two-STAT4 Gene Polymorphisms and Rheumatoid Arthritis in Turkish Population? - Berrin YÜKSEL; Şebnem ATAMAN; Deniz EVCİK and Saime AY and Mine MUMCUOĞLU and Beyza ERDOĞAN5 (Archives of Rheumatology, 2014)
Objectives: The aim of this study was to investigate whether the rs7574865 and rs10181656 single nucleotide polymorphisms of the STAT4 gene confer susceptibility to rheumatoid arthritis (RA) in the Turkish population. Patients and methods: Genomic DNA was obtained from 140 patients with RA and 138 ethnically matched healthy controls. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis was used to identify the rs7574865 and rs10181656 polymorphisms in the third intron of the STAT4 gene. The genotype distributions and allelic frequencies of these two polymorphisms were compared between RA patient group and controls. The relationship between the genotype distributions of the two single nucleotide polymorphisms and the clinical and laboratory data of RA patients was investigated. Results: There were no significant differences between the groups regarding the allele frequencies of the rs7574865 and rs10181656 polymorphisms (p=0.654 and p=0.594, respectively) and the genotype distributions of the two polymorphisms (p=0.686 and p=0.467, respectively). There was no correlation between the genotype distributions of the rs7574865 and rs10181656 polymorphisms of the STAT4 gene and the clinical features and laboratory findings of the RA patients. Conclusion: Our study results indicated that the rs7574865 and rs10181656 polymorphisms in the STAT4 gene were not associated with a susceptibility to RA in the Turkish population.